Household budget: Impacts of incomes on consumption - Đikanović, Danilo (Journal of Economic Development, Environment and People, 2018)
This research is undertaken to explain the relation between several types of income and total personal consumption. Based on research method used, which is descriptive and regression analyses, the high influence of incomes on consumption is proven. Through various statistical results it is shown in which extent the correlation is relevant and how it is concluded that the chosen variables are sufficient enough to explain the variation of the level of consumption through time. The main goal of this research is to discover what lies behind consumption and to  understand the households as main consumption units on the market. Gained results are based on data analysis, in which the independent variables are ''Income from pension insurance'', ''Income from property'', ''Income from small business'' and ''Wages and salaries'', while the dependent variable is ''Personal consumption''. After testing all assumptions of linear regression and conducting the entire analysis, it is concluded that every independent variable is good in explaining the value of the dependent variable ''Personal consumption''. The statistical unit on which the analysis is based is a household, so statistics shown in this research are useful for understanding the essence of a budget in household economies.